The meaning and impact on well-being of bespoke dancing sessions for those living with Parkinson’s - Elizabeth Norton; Ann Hemingway; Caroline Ellis Hill (International Journal of Qualitative Studies on Health & Well-Being, 2023)
Purpose This paper presents qualitative research findings from the evaluation of a Parkinson’s Dance well-being venture in the UK. Methods Qualitative data was gathered to see how bespoke dancing sessions helped people with Parkinson’s (PwP) to manage their conditions and improve their lives and prospects. Principles of a participatory approach were incorporated and methods included semi-structured interviewing, researchers participant observation and an elicitation-based activity. Nineteen PwP, six carers, four dance artists and seven helpers participated in the study. Results Participating in Parkinson’s Dance sessions meant that PwP could experience the possibilities to dance, develop a “can do” attitude, experience fun, enjoyment, social connection, exercise, movement to music, improvement and/or maintenance of their balance, suppleness, coordination and confidence with movement, symptoms being pushed back and ability to learn new things. Conclusions Our findings add to the evidence-base about the benefits of dance for people experiencing Parkinson’s and through novel application of the Life-world based well-being framework of K. T. Galvin and Todres (2011) we propose a theoretical basis for Parkinson’s Dance as a resource for well-being. There is scope to consider application of the well-being framework to other arts activities and as the basis of an arts and well-being evaluation tool.